Job Motivation as Predictor of Research Productivity of Librarians in Public Universities in South-West, Nigeria - FASAE, Joseph Kehinde; UWAIFO, Stephen Osahon (Ilorin Journal of Education, 2024)
The study investigated the influence of job motivation on the research productivity of librarians in public universities in South-west, Nigeria. The research adopted a correlational type of descriptive research design. The population of the study is 265 librarians in the libraries of 18 public universities. Total enumeration sampling techniques was used for the study. A structured questionnaire was the research instrument used for data collection that was validated by experts in this field. The reliability of the instrument was 0.84. Data collected were analysed using statistical mean, standard deviation, and Pearson Product Moment Correlation Coefficient (PPMCC), with a criterion mean of 2.50. The finding of the study revealed that research productivity of librarians between 2017-2022 was low. It was revealed that the extent of job motivation on the research productivity of librarians was high. Also, there is a significant relationship between job motivation and research productivity of librarians in public universities in South-west Nigeria. The study concluded that job motivation is an important factor that can predict the research productivity of librarians in public universities in South-west, Nigeria. It was therefore recommended that university management should sustain high levels of motivation in place for librarians by creating a supportive and inclusive work environment that values their contributions.